Differences in competitive participation according to player's position in formative basketball - Ortega, E.; Cardenas, D.; Sainz de Baranda, P.; Palao, J. M. (Journal of Human Movement Studies, 2006)
The purpose of this study was to analyze and compare the way that players participate during basketball competition in formative years according to player position. One hundred and eighty-four under-16 basketball players (37 point-guards, 32 off-guards, 61 small-forwirds, 21 power-forwards, and 36 Centers) were analyzed during 24 garnes. The analyzed variables were: play tirne, time of ball possession, and nurnber of times that ball possession was obtained. The results showed differences in play time between the point-guards and centers with the rest of players. There were differences in modality of ball possession between the point-guards and the rest of the players. The point-guards were the players that had the most tirne with ball possession. These results showed an eazly specialization of the players because each player's position realized only specific functions, which goes against a multi-faceted formation proper for youth.